Advances in the Endoscopic Management of Obesity - Jason Behary; Vivek Kumbhari (Gastroenterology Research and Practice)
Obesity has become a worldwide epidemic with significant impact on quality of life, morbidity, and mortality rates. Over the past two decades, bariatric surgery has established itself as the most effective and durable treatment for patients with obesity and its associated comorbidities. However, despite the use of minimally invasive techniques, bariatric surgery is associated with complications in approximately 15% of patients, has a substantial cost, and is used by only 1% of patients who are eligible. Therefore, there is a need for effective minimally invasive therapies, which will be utilized by the large proportion of obese patients who are in desperate need of treatment but are not receiving any. Endoscopic approaches to the management of obesity have been developed, with the aim of delivering more effective, durable, and safer methods of weight reduction. In this paper, we review currently available and future endoscopic therapies that will likely join the armamentarium used in the management of obesity.